Pengembangan Sistem Informasi Lowongan Kerja di Career Center Universitas Darma Persada - Yahya, Yahya; Susilawati, Endang Ayu; Novianti, Eva; Rahmadanti (Prodi Teknologi Informasi Universitas Darma Persada, 2025)
Career centers play a vital role in bridging the gap between higher education and the workforce by helping students and alumni access job opportunities and develop relevant skills. At Universitas Darma Persada, the career center faced challenges in disseminating job vacancy information efficiently due to time constraints and limited distribution methods, primarily via Instagram. This study aims to design and develop a web-based job vacancy information system to improve accessibility and communication between job seekers and employers.The uniqueness of this research lies in the development of a role-based job portal system that integrates multiple user roles, namely job seekers (students and alumni), career staff, and employers, into a single digital platform. The objective is to accelerate job vacancy publication, facilitate job applications, and streamline employer access to candidate data.This study adopts the Waterfall methodology, including stages of requirement analysis, system design, implementation, and testing. Data were collected through observation, interviews, and literature review. The final system was developed using Visual Studio Code, PHP, MySQL, and other web development tools.The results show that the system successfully reduces delays in job vacancy announcements, expands reach beyond Instagram, and provides a more structured and interactive recruitment process. Employers can post jobs and review CVs, while job seekers can apply directly and track their application status. The system has proven effective in enhancing the career center’s role in graduate employability support.